Hadis sebagai Sumber Sejarah - Wahyuddin G (Jurnal Adabiyah: Humanities and Islamic Studies, 2009)
One of the meaning of history is a science that tries to inherit knowledge about the past of certain society. Historians try to research the past through various ways or methods. From the perspective of methodology, history source has a significant role of all research processes and stages of history, including heuristic, criticism, interpretation, and historiography. Methodology used in prophetic tradition includes critics on chain and text, but this methodology is not followed by historiography as it is in history research. Criticism methods of the prophetic tradition conducted by prophetic tradition scholars are able to give the high accuracy results provided those methods performed carefully and thriftily. Thus, the selected prophetic tradition is very reliable as a history source not as a history book.